Menciptakan Kepuasan Pelanggan dan Minat Beli Ulang: Studi Empiris Pada Bisnis Wisata Kuliner Kreatif - Siti Zulaikha Wulandari; Hanisa Lail Shafirayana; Sri Murni Setyawati (Soegijapranata Catholic University, 2021)
The culinary tourism business provides a very potential opportunity for businessman. Competition among creative culinary businesses is currently getting more fierce, so it is important for the business to understand the variables that affect customer satisfaction and repurchase intention. This research was conducted to see the influence of several variables that are perceived affecting repurchase intention that mediated by customer satisfaction in a creative culinary tourism business. In particular, the model in this study was developed to test the effect of product quality, service quality, price, and servicescape on customer satisfaction that consequently influence repurchase intention. Multiple regression analysis were applied to analyse the answer of 107 respondents selected using purposive sampling method. The research results were obtained and showed the significant influence of product quality, service quality and servicescape on customer satisfaction. Whereas the price did not show a significant effect. In turn customer satisfaction significantly influence customer repurchase intention. In-depth discussion of the research finding was discussed in the section of results and discussion.